2011
DOI: 10.1124/jpet.110.178079
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Matrix Metalloproteinase-Mediated Proteolysis of Neural Cell Adhesion Molecule in the Development of Cerebral Ischemic Neuronal Damage

Abstract: Neural cell adhesion molecule (NCAM) is a membrane protein abundantly expressed in the central nervous system. Recently, it has been reported that dysfunction of NCAM is linked to human brain disorders. Furthermore, NCAM is one of the proteolysis targets of matrix metalloproteinase (MMP), whose activation is implicated in neuronal damage. The aim of this study was to elucidate the involvement of MMP-mediated proteolysis of NCAM in the development of ischemic neuronal damage. Male ddY and MMP-9 knockout (KO) C5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 45 publications
2
30
0
Order By: Relevance
“…Decreased full-length NCAM180 has been described in mice 1 day after middle cerebral artery occlusion (Shichi et al, 2011). Moreover, it has been shown that in the processes of demyelinating neuroinflammation resulting from the autoimmune encephalomyelitis, the level of MMP-2 was significantly increased in hippocampus, which was accompanied by reduced levels of NCAM (Jovanova-Nesic and Shoenfeld, 2006).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Decreased full-length NCAM180 has been described in mice 1 day after middle cerebral artery occlusion (Shichi et al, 2011). Moreover, it has been shown that in the processes of demyelinating neuroinflammation resulting from the autoimmune encephalomyelitis, the level of MMP-2 was significantly increased in hippocampus, which was accompanied by reduced levels of NCAM (Jovanova-Nesic and Shoenfeld, 2006).…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies have demonstrated that several metalloproteases, such as MMP-2 and MMP-9, as well as the ADAM family of metalloproteases, target NCAM (Brennaman et al, 2014;Hinkle et al, 2006;Hübschmann et al, 2005;Shichi et al, 2011). It has also been shown that inhibition of MMP-2 and MMP-9 prevents NCAM shedding, indicating the roles of these MMPs in NCAM cleavage (Hübschmann et al, 2005;Shichi et al, 2011). Moreover, ADAM-10-dependent shedding of NCAM has been extensively studied, and the second fibronectin-type III domain of NCAM has been shown to be a target for ADAM-10 cleavage (Brennaman et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, recent reports have revealed the breakdown of Neural Cell Adhesion Molecule (NCAM) as a functional consequence of injury caused by middle cerebral artery occlusion. 135,136 A noteworthy finding in the N1E-115 neuroblastoma cell line was the involvement of TRPM7 in the development of podosomes. While these actin-based protrusions have been suggested to contribute toward tissue invasiveness during malignancy, 137 they are also thought to be mediators of cell adhesion.…”
Section: Trpm7-dependent Ischemic Cell Death: Lingering Questions Andmentioning
confidence: 99%